SELEKSI DAN UJI ANTIBAKTERI AKTINOMISETES ASAL TANAH GAMBUT RIMBO PANJANG KAMPAR RIAU TERHADAP Escherichia coli DAN Salmonella typhi - Siti Suryani; Rodesia Mustika Roza; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Actinomycetes is one of microorganisms that can be used as a natural antibiotic. Metabolites produced by actinomycetes have antagonistic activity on bacteria, therefore it can be used as antibacteria. The purposes of this study were to select and test the antibacterial activity of actinomycetes isolated from peat soil in Desa Rimbo Panjang Kabupaten Kampar Riau to inhibit the growth of Escherichia coliand Salmonella typhi. This study was conducted from December 2013-January2014 at the Microbiology Laboratory, University of Riau. Serial dilutions and pour plate method used for isolation of actinomycetes while agar disk method used for antibacterial test. The result found a total of 24 actinomycetes isolates, 10 isolates inhibiting E. coli, and 16 isolates inhibiting S. typhi. The inhibition zone diameter of E. coliand S. typhi were 8,3 to 16,9 mm and 7,8 to 12,9 mm, respectively.